Fabrication and Characterization of Ocular Phase Transition Systems for Blepharitis: A Novel Approach - Verma, Deepali; Kaul, Shreya; Jain, Neha; Nagaich, Upendra (Drug Delivery Letters, 2020)
Introduction: In the present research, erythromycin estolate loaded in-situ gel was formulated and evaluated for blepharitis in order to improve its therapeutic efficacy, precorneal residence time of the system and to enhance the ocular bioavailability. Materials and Methods: The developed formulation was characterized by several parameters viz. FTIR, clarity, pH, gelation temperature, rheological studies, drug content, in vitro drug release studies, transcorneal permeation studies, bioadhesion studies, isotonicity and stability studies. Results: The optimized formulation exhibited non-fickian release diffusion with a sustained release of drug 82.76 ± 0.94% up to 8h and drug content 93.64%. Isotonicity revealed that the formulation was isotonic in nature and there was no shrinkage and busting of cells. Bioadhesion study was performed to check the adherence of the prepared in situ gel to the corneal surface for 4h. Ex vivo transcorneal permeation was observed to be significantly higher when compared with market eye drops. Histopathological studies were conducted to confirm the presence of normal ocular surface tissues by maintaining their morphological structures without causing damage to the tissues. The formulation was nonirritant as confirmed by the HET-CAM test. Stability studies and accelerated stability studies were conducted for 13 weeks and 26 weeks respectively and formulations were analyzed for the visual appearance, pH, viscosity, gelling capacity, drug content and in vitro drug release and results showed no change in the formulations. Conclusion: The formulation was therapeutically efficacious, sterile, stable and provided controlled release over a period of time. The developed system could be a viable alternative to conventional eye drops for treatment of various ocular diseases.
Keywords: histopathological studies